Ligand exchange processes on solvated beryllium cations VII - Water exchange on cationic [Be(H 2O) 3(L n)] 2+n (L n: 4-O-Py -, Py, 4-(Py)-Py +, 3,5-(Py) 2-Py 2+, 3,4,5-(Py) 3-Py 3+) - Walther, Markus; Puchta, Ralph (RSC Advances, 2012)
The water exchange reactions on [Be(H 2O) 3(L n)] 2+n (L n: 4-O-Py -, Py, 4-(Py)-Py +, 3,5-(Py) 2-Py 2+, 3,4,5-(Py) 3-Py 3+) were investigated through quantum chemical calculations (B3LYP/6-311+G**). While in all cases an associative interchange mechanism was found, the associative character was found to increase with increasing charge on the overall system, which in turn is governed by the charge on the ligand L n. Including the CPCM solvent model into the system decreases the amplitude of the energetic effects, but leaves the general trend intact. Furthermore, the binding energy of a fourth water molecule and the overall exchange activation energy were found to increase with the overall charge on the system. The structures are also influenced by the charge, but to a smaller extent. The Be-O distances to the second coordination sphere water molecule and the distances to the entering/leaving water molecules in the transition state are significantly shortened in the higher charged systems. These effects can be attributed to electrostatic interactions. © 2012 The Royal Society of Chemistry.
CRIS-Team Scopus Importer:2026-01-22